Penentuan Viabilitas Polen dan Reseptif Stigma pada Melon (Cucumis melo L.) serta Hubungannya dengan Penyerbukan dan Produksi Buah - Hasanuddin Hasanuddin (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
The research aims are (1) to know the duration of stigma receptive and pollen viability maximally as guidance in artificial pollination process in Melon; (2) to know the degree of success of artificial pollination and its relation with production (quantity) and quality (weight) of Melon, has been conducted. The research method is used to determine pollen viability and receptive stigma. Therefore, experimental method is used to test the success of artificial pollination toward production and fruit quality. The obtained data was analyzed by Anava and regression. The result indicated that (1) Receptive stigma maximum occurred by the time the flower opens; (2) Pollen viability maximum occurred a day after the flower opens; (3) Quantity and quality fruit through the process of artificial pollination increase 35,51 % compared to natural pollination.